Failure of motor function—A Developmental Embodiment Research perspective on the systemic effects of stress - Krüger, Melanie; Lux, Vanessa (Frontiers in Human Neuroscience, 2023)
Humans are capable to skillfully perform a huge variety of complex movements seemingly effortless and to flexibly adjust movement execution to ever-changing environmental conditions, often without apparent differences in the movement outcome. This impressive ability has sparked scientific interest in the mechanisms underlying movement execution for decades. In this perspective article, we argue that investigating the processes and mechanisms leading to failure of motor functions is a fruitful approach to advance the field of human motor neuroscience and beyond. The study of failure of motor function in specific populations (patient groups, skilled experts) has already provided tremendous insight in the systemic characteristics and multi-level functional dependencies of movement execution. However, particularly the transient failure of function in everyday motor actions remains a blind spot. Coming from the perspective of Developmental Embodiment Research, we argue that the integration of a developmental embodiment and lifespan perspective with existing systemic and multi-level methodological approaches of failure of function analyses provides an integrative, interdisciplinary framework, which will allow us to overcome this shortcoming. We further suggest that stress-induced failure of motor function situations might represent a promising starting point for this endeavor. Identifying the involved cross-level functional dependencies of acute and chronic stress on transient and persistent motor functioning would further advance our knowledge on the mechanisms underlying movement execution, and would allow to identify targets for intervention and prevention across the whole spectrum of motor function and failure.